Devaluation Crises and the Macroeconomic Consequences of Postponed Adjustment in Developing Countries. (IMF Working Papers; Working Paper ;, 1989)
This paper develops a small analytical model to explore the relationship between the dynamics of macroeconomic adjustment and the timing of the implementation of an adjustment program featuring a nominal devaluation. The effects of postponing adjustment depend on the source of the original shock. In the case of a fiscal expansion, postponement implies a larger eventual devaluation and greater deviations of macroeconomic variables from their steady-state values. For adverse terms of trade shocks, postponement does not affect the size of the eventual devaluation, but does magnify the degree of post-devaluation overshooting by key macroeconomic variables.